The Pillars of Hercules as a bathymetric barrier to gene flow promoting isolation in a global deep‐sea shark (Centroscymnus coelolepis). Issue 24 (7th December 2015) - Catarino, Diana; Knutsen, Halvor; Veríssimo, Ana; Olsen, Esben Moland; Jorde, Per Erik; Menezes, Gui; Sannæs, Hanne; Stanković, David; Company, Joan Baptista; Neat, Francis; Danovaro, Roberto; Dell'Anno, Antonio; et al.
Abstract: Knowledge of the mechanisms limiting connectivity and gene flow in deep‐sea ecosystems is scarce, especially for deep‐sea sharks. The Portuguese dogfish ( Centroscymnus coelolepis ) is a globally distributed and near threatened deep‐sea shark. C. coelolepis population structure was studied using 11 nuclear microsatellite markers and a 497‐bp fragment from the mtDNA control region. High levels of genetic homogeneity across the Atlantic ( Φ ST  = −0.0091, F ST  = 0.0024, P  >   0.05) were found suggesting one large population unit at this basin. The low levels of genetic divergence between Atlantic and Australia ( Φ ST  = 0.0744, P  <   0.01; F ST  = 0.0015, P  >   0.05) further suggested that this species may be able to maintain some degree of genetic connectivity even across ocean basins. In contrast, sharks from the Mediterranean Sea exhibited marked genetic differentiation from all other localities studied ( Φ ST  = 0.3808, F ST  = 0.1149, P  <   0.001). This finding suggests that the shallow depth of the Strait of Gibraltar acts as a barrier to dispersal and that isolation and genetic drift may have had an important role shaping the Mediterranean shark population over time. Analyses of life history traits allowed the direct comparison among regions providing a complete characterization of this shark's populations. Sharks from the Mediterranean had markedly smaller adult body size and size at maturity compared to Atlantic and Pacific individuals. Together, these results suggest the existence of an isolated and unique population of C. coelolepis inhabiting the Mediterranean that most likely became separated from the Atlantic in the late Pleistocene.